2018
DOI: 10.1073/pnas.1806376115
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism mediates disease tolerance in cerebral malaria

Abstract: Sickness behaviors are a conserved set of stereotypic responses to inflammatory diseases. We recently demonstrated that interfering with inflammation-induced anorexia led to metabolic changes that had profound effects on survival of acute inflammatory conditions. We found that different inflammatory states needed to be coordinated with corresponding metabolic programs to actuate tissueprotective mechanisms. Survival of viral inflammation required intact glucose utilization pathways, whereas survival of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 48 publications
3
64
0
Order By: Relevance
“…We have previously shown that while administration of 2-DG to animals challenged with Poly I:C or influenza resulted in driving the unfolded protein response toward neuronal cell death leading to enhanced mortality, administration of 2-DG to animals challenged with LPS or Listeria resulted in enhanced survival by mechanisms which are yet to be fully identified but independent of the magnitude of the inflammatory response (12). We have also recently shown using mouse models of malaria that 2-DG protected animals from cerebral malaria by affecting hemostasis while others have shown that it potentiates mortality in malarial models of fatal anemia (57,58). It is likely that the composite outcome of 2-DG depends on the given set of biological processes that require glucose in any particular organismal state.…”
Section: Discussionmentioning
confidence: 96%
“…We have previously shown that while administration of 2-DG to animals challenged with Poly I:C or influenza resulted in driving the unfolded protein response toward neuronal cell death leading to enhanced mortality, administration of 2-DG to animals challenged with LPS or Listeria resulted in enhanced survival by mechanisms which are yet to be fully identified but independent of the magnitude of the inflammatory response (12). We have also recently shown using mouse models of malaria that 2-DG protected animals from cerebral malaria by affecting hemostasis while others have shown that it potentiates mortality in malarial models of fatal anemia (57,58). It is likely that the composite outcome of 2-DG depends on the given set of biological processes that require glucose in any particular organismal state.…”
Section: Discussionmentioning
confidence: 96%
“…Our understanding of how, in the context of moderate to high exposure to parasite and host components in the bloodstream of malaria-infected subjects, the majority of clinical cases lack overt clinical disease and complications is still limited (Sinton, 1938;Crompton et al, 2014). In addition to evolutionary human adaptation to malaria parasites that confer host resistance (Júnior et al, 2010;Piel et al, 2013;Vale, 2018;Wang et al, 2018), multiple mechanisms have been proposed to explain malaria tolerance. In this study, we observed that IFN-γ and serum kynurenines increase to both control the infection and to avoid host immunopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium parasites have lost multiple genes involved in nutrient synthesis and have to compete with their hosts for essential nutrients (Gardner et al, 2002). Both liver and blood stage malaria parasites scavenge host glucose for their energetic needs (Meireles et al, 2016;Olszewski and Llinas, 2011;Stanway et al, 2019;Wang et al, 2018). However, little is known about the crosstalk between glucose metabolism of Anopheles and that of Plasmodium.…”
Section: Discussionmentioning
confidence: 99%